The Analysis of the Relationship Between Compliance Activities of Diabetes Mellitus Patients and the Event of Diabetic Ulcus - Maria Putri Sari Utami; Amanda Marselin; Fajar Agung Dwi Hartanto (GLOBAL HEALTH SCIENCE GROUP, 2021)
Diabetes Mellitus is a chronic disease that causes various complications, one of which is diabetic ulcers. This requires maximum management and compliance of DM patients. Activity compliance is one of the factors that influence the incidence of diabetic ulcers. This study is a correlation study that aims to determine the relationship between the activity compliance of diabetes mellitus patients with the incidence of diabetic ulcers. The research method used is a cross sectional study. The sampling method used consecutive sampling technique with a total sample of 22 samples. The research site was conducted in five wound care clinics spread across the district of Yogyakarta Province. Based on the results of the study, it is known that the highest age is 56-65 years (50%), the highest level of education is at the junior high and high school levels (27.3%), the most type of work is self-employed (40.9%), the most type of DM is DM type 2 (68.2%), the duration of suffering 10-15 years (50%), the highest degree of ulcer was grade 1 (45.5%), and as many as 77.3% patients were not obedient in carrying out physical activities. Based on the results of the correlation test, it is known that activity compliance is not associated with the incidence of diabetic ulcers (p value>0.05). Activity compliance is not associated with diabetic ulcers.